398 Right ventricular cardiogenic shock induced by propafenone intoxication: a case report. (8th December 2021) - Maurina, Matteo; Bertoldi, Letizia; Briani, Martina; Chiarito, Mauro; Reimers, Bernhard; Corrada, Elena
Abstract: Aims: Propafenone is a Class 1C antiarrhythmic drug recommended in the treatment of supraventricular or ventricular tachycardia and paroxysmal atrial fibrillation (AF). Most common cardiological features associated with propafenone intoxication include heart failure and conduction disturbances while other clinical findings range from nausea and vomiting to seizures and coma. Methods: We report a case of atypical presentation of propafenone intoxication occurred in 88-year-old woman who presented at Emergency Department with severe ECG abnormalities and prevalent acute right ventricular with massive tricuspidalic regurgitation and cardiogenic shock. The patient underwent urgent coronary angiography that revealed a stable 90% coronary plaque that was treated with a single stent and then brought to Intensive Care Unit where she was successfully treated with inotropic and mechanical circulatory support (intra-aortic balloon pump, IABP). Results: The patient progressively achieved hemodynamic stability with complete ECG normalization and biventricular function recovery. Conclusions: Our case further expands the vast spectrum of presentations of Class 1c antiarrhythmic drugs overdose. In an emergency setting it is difficult to rule out other causes of cardiogenic shock but propafenone toxicity needs to be suspected in every case of hemodynamic instability in patients in chronical treatment. Patients in chronical treatment with propafenone who have kidney or liver dysfunction might be at higher risk of drug accumulation: in such cases, the real utility of propafenone must be evaluated before therapy initiation.